Speech-aid prosthesis in velopharyngeal incompetency patient with cleft palate: can speech aids be applicable for adult patient? - Dong-Cheol Kang; Jung-Ho Park; Hyun Seok; Jin-A Baek; Da-Wa Kim; Seung-O Ko (SpringerOpen, 2021)
Abstract Background Velopharyngeal incompetence (VPI) therapy for cleft palate (speech therapy alone, speech therapy using speech aids, or combined therapy such as speech therapy using a pharyngeal flap), is more effective in younger patients than in adult patients. Speech therapy is known as very difficult for patients who still have VPI as an adult. Because of the possibility of subsequent speech disorders, the timing of surgery for cleft palate is accelerating. Herein, we present a case of an adult with articulation disorder due to VPI who was treated by speech therapy and a speech-aid prosthesis. Case presentation A woman who underwent cleft palate surgery at 8 years of age still had difficulty with articulation due to VPI as a 24-year-old adult because of a lack of continuous speech therapy. We decided to use a speech-aid application using palatal lift, and a reduction program was conducted four times, along with simultaneous speech therapy, over a period of 1 year and 7 months. During the therapy period, she was able to speak normally within a relatively short period of time, and after implementation of the reduction program, the therapy was completed by completely removing the device. Long-term observations have shown normal speech function without recurrence, even after the device was removed. Conclusion As seen in this case, speech therapy using speech aids can show a good result for adult patients with cleft palate who missed the usual timing for the treatment of articulation disorders, depending on the situation. Therefore, it is hereby reported as a therapy option worthy of consideration.